Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Pegawai - Siswo Susilo (LPPM STIE KRAKATAU, 2018)
Target This study ekplanotory which describes the effect of Organizational Culture and Work Discipline on employee performance in South Lampung District Health Office. A population of 130 people and a sample is taken based on the formula Slovin thus obtained a sample of 97 respondents in this case the employee at the institution in question. Methods Quantitative and Qualitative data analysis. Quantitative analysis is used to analyze the statistical hypothesis test in order to conduct research on the data obtained. The calculation process using SPSS software while the qualitative analysis carried out for the approach to the management theories, especially the approach factor Organizational Culture, Work Discipline and Employee Performance The results showed Organizational Culture influence on employee performance amounted to 53.6% and Work Discipline influence on employee performance amounted to 41.3% whereas the effect of variables simultaneously or together 53.6%